Teacher's problems and solutions in implementing student-centered learning in SMAN Bali Mandara Singaraja - Putu Erna Adnyani; I Putu Ngurah Wage Myartawan; I Nyoman Pasek Hadi Saputra (Universitas Islam Malang, 2021)
This qualitative descriptive study aimed at analyzing teachers' problems and solutions in implementing Student-centered Learning. This study involved an English teacher in SMA N Bali Mandara Singaraja. The instruments of this study consisted of voice recorder, field notes, interview guide, and researcher as the main instrument. The obtained data were analyzed using Miles and Huberman (1994) theory which consisted of data collection, data reduction, data display and conclusion drawing/verification. The results showed that the teacher's problems included problems caused by students, teacher, and facilities to support learning. The teachers' solutions to solve the problems were by identifying the students' ability, motivating students personally, doing the class management well, using